SIMULASI GERBANG DASAR LOGIKA DALAM APLIKASI - Hoiriyah, Hoiriyah (Jurnal Teknik Informatika dan Elektro, 2020)
It is no longer a secret that all science is currently developing and has technological advances that cannot be denied, especially in digital technology which is currently popular, one of which is a digital electronic system that is composed of logic gates so that it becomes a digital system formed from logic elements. the smallest is the logic gate (Logic Gate): OR, AND and NOT where the circuit work process on this logic gate uses Boolean algebra principles. In its implementation it is rather difficult to provide an understanding of logic gates manually or in theory to the public and the general public in understanding gate circuits electronics to understand the functions and uses of logic gates in electronic circuits with EWB (Electronic WorkBanch) as an electronic computer software that can be used to simulate the workings of an electronic circuit, both analog and digital. The EWB application is very helpful in providing an indirect understanding of understanding basic logic gate circuits as simulations in applications to reduce possible dangerous risks, with this application it makes it easy to know the conditions you want to design and create before implementing them in real form..